Evaluasi Efektivitas Mikoriza dan Pupuk Organik terhadap Pengendalian Serangan Fusarium oxysporum f.sp. Cepae pada Bawang Putih - Supyani Supyani; Dwiwiyati Nurul Septariani; Zahra Tazkiyatun Haqiki; Hadiwiyono Hadiwiyono (Universitas Sebelas Maret, 2024)
The main problem in garlic cultivation was root rot disease caused by Fusarium oxysporum f.sp. cepae. Environmentally friendly control following sustainable agriculture can be used to increase plant resistance by providing biological fertilizers such as mycorrhizae and organic fertilizers such as compost and husk charcoal. This research aimed to evaluate the effectiveness of the application of mycorrhizae and organic fertilizers against Fusarium oxysporum f.sp. cepae. The research was conducted from June to November 2021 at the Tawangmangu Horticultural Seed Garden in Jl. Raya Tawangmangu, Beji, Tawangmangu, Karanganyar. Laboratory test was conducted from December 2021 to January 2022 at Laboratory of Plant Pests and Diseases and Laboratory of Soil Chemistry, Faculty of Agriculture, Sebelas Maret University. The method used was completely randomized design with a combination of mycorrhizae treatment (2 gr plant -1), compost fertilizer (16 ton ha-1), and husk charcoal fertilizer (6 ton ha-1). The data obtained were analyzed using analysis of variance and then continued with the Duncan’s Multiple Range Test. The results showed that mycorrhizae gave 22.95% effectiveness in wilting control and 20.93% in tuber rot control. Organic fertilizers provide the wilting effectiveness control by 9.27% (compost) and 8.06% (husk charcoal), as well as tuber rot effectiveness control by 27.91% (compost) and 25.58% (husk charcoal). The combination of mycorrhizae and organic fertilizers gave the highest wilt control effectiveness of 26.07% in the combination of mycorrhizae, compost, and husk bran. The effectiveness of tuber rot control was found in the combination of Mycorrhizae and compost, which was 34.88%.